Partial replacement of municipal solid waste incineration bottom ash for cement substitution in brick - Roslidawati Binti Ayub (School of Environmental Engineering, University Malaysia Perlis, 2014)
The objective of this research are study the engineering properties of brick with the replacement of bottom ash as cement substitution subject to different curing regime. Bottom ash used are brought from incineration plant in Pulau Pangkor.